1992
DOI: 10.1080/00480169.1992.35696
|View full text |Cite
|
Sign up to set email alerts
|

A slaughterhouse survey of lung lesions in goats

Abstract: A survey of the lungs from 4284 goats killed at a slaughterhouse in the North Island of New Zealand during the winter of 1990 revealed only ten cases of non-parasitic bronchopneumonia. However, 41% of the lungs had lesions consistent with infection by Muellerius capillaris, 33% with Dictyocaulus filaria, and 8% with both species. The prevalence of parasitic lesions increased with age. The carcasses of goats with mild to severe Dictyocaulus filaria lesions were from 0.81 to 1.52 kg lighter than those without th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 14 publications
2
10
0
Order By: Relevance
“…cupilluris induced lesions is that the worm lives within alveoli but is enclosed in grossly visible hemorrhagia-to-greyish nodules that are mostly located subpleurally and may be diffuse, involving the entire lung. The findings in this study agree with other descriptions of this condition in sheep (BERESFORD-JONES, 1971 ;PIRIE, 1979;ARMOUR, 1983ARMOUR, , 1991DUNGWORTH, 1985;KIMBERLING, 1988;YATES, 1988 (PIRIE, 1979;ARMOUR, 1983ARMOUR, , 1991. By contrast, this parasite has been reported to have significant inhibitory effects on weight gain in goats (NIMMO, 1979).…”
Section: Bacteriologysupporting
confidence: 92%
See 1 more Smart Citation
“…cupilluris induced lesions is that the worm lives within alveoli but is enclosed in grossly visible hemorrhagia-to-greyish nodules that are mostly located subpleurally and may be diffuse, involving the entire lung. The findings in this study agree with other descriptions of this condition in sheep (BERESFORD-JONES, 1971 ;PIRIE, 1979;ARMOUR, 1983ARMOUR, , 1991DUNGWORTH, 1985;KIMBERLING, 1988;YATES, 1988 (PIRIE, 1979;ARMOUR, 1983ARMOUR, , 1991. By contrast, this parasite has been reported to have significant inhibitory effects on weight gain in goats (NIMMO, 1979).…”
Section: Bacteriologysupporting
confidence: 92%
“…By contrast, this parasite has been reported to have significant inhibitory effects on weight gain in goats (NIMMO, 1979). Moreover, an abattoir-based survey by VALERO et al (1992) indicated that carcasses of goats with more than 10 pulmonary nodular lesions of M . cupilluris were 0.75 kg lighter than those without the lesions.…”
Section: Bacteriologymentioning
confidence: 99%
“…Many pathological features of the lungs in domestic and wild ruminants with protostrongylid infections observed in the present study have been described by other researchers [8, 13, 14, 16, 17, 19–24]. However, limited attention has been paid to the parasite-host interaction within the inflammatory foci.…”
Section: Discussionsupporting
confidence: 60%
“…However, according to our data many of the alveolar septa remain without visible morphological abnormalities despite the presence of a large number of parasites in the alveolar lumen. According to the results of Valero et al [13] the lesions in goats associated with M. capillaris infection are nodular, disseminated mostly on the caudo-dorsal aspects of the lungs and their prevalence increase with age. The data of Berrag et al [8] are similar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation